A study of male and female managers between economic sectors of Latvia using EU-SILC survey - Vasina, Sabine Anete; Sloka, Biruta (University of Latvia, 2020)
Gender pay difference has been a widely recognized issue worldwide and one of the most popular research topics between various researchers, as there is still a relatively low share of women representing roles in senior management. The aim of this study is to analyse recent scientific findings on wage gap between male and female managers, and to explore possible occupation segregation in Latvia, as well as employment differences between male and female managers in the context of economic sectors and salary levels. Research methods used to prepare this particular study are analysis of the following: scientific publications, statistical data obtained from the database of European Union Statistics on Income and Living Conditions (EU-SILC). The databases are analysed using Statistical Package for Social Sciences (SPSS) and the functions provided, especially data filtration and case selecting, crosstabulations, descriptive statistics and frequencies. The results indicate that based on researches done before the wage gap in upper management and executive roles can be formed due to low women representation, although some still argue that gender inequality exists especially in context of occupational segregation. Data analysis shows the presence of horizontal gender segregation in Latvia, as well as employment differences between various economic sectors in context of managers.
Keywords: wage gap; managers; gender segregation; EU-SILC; Research Subject Categories::SOCIAL SCIENCES::Business and economics